2000
DOI: 10.1007/s11883-000-0049-5
|View full text |Cite
|
Sign up to set email alerts
|

Dietary fiber and cardiovascular disease: Experimental and epidemiologic advances

Abstract: Recently reported experimental studies offer insight into the various mechanisms through which dietary fiber may reduce the risk of cardiovascular disease (CVD) in humans. Although most work has focused on traditional risk factors, studies have begun to explore less studied areas of risk such as fibrinolysis. Epidemiologic results have consistently demonstrated inverse associations between dietary fiber, particularly cereal fiber and whole grain foods, and the development of CVD morbidity and mortality. These … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
32
0
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(33 citation statements)
references
References 49 publications
0
32
0
1
Order By: Relevance
“…Several mechanisms have been proposed by which dietary fiber may reduce CHD mortality risk (16). Soluble fibers increase the rate of bile acid excretion by binding bile acids in the small intestine, thereby reducing serum total and LDL cholesterol (43)(44)(45).…”
Section: Discussionmentioning
confidence: 99%
“…Several mechanisms have been proposed by which dietary fiber may reduce CHD mortality risk (16). Soluble fibers increase the rate of bile acid excretion by binding bile acids in the small intestine, thereby reducing serum total and LDL cholesterol (43)(44)(45).…”
Section: Discussionmentioning
confidence: 99%
“…The underlying mechanisms of the effect of dietary fiber on the cardiovascular system remain poorly understood, although previous studies have shown that fiber intake can affect blood pressure, systemic inflammation, serum lipid concentrations, postprandial absorption of carbohydrates, insulin sensitivity, fibrinolysis, coagulation, and endothelial cell function (15)(16)(17)(18)(19)(20)(21).…”
Section: Introductionmentioning
confidence: 99%
“…The fiber content is beneficial as fiber in food helps eliminate bile acids, lower body cholesterol and creates variation in feacal bulk and transit time [16]. High fiber diet intake prevents diet related diseases like cardiovascular disease, cancer of the colon and diabetes [25]. Diet with high fiber content have been used for weight control and fat reduction as it provides satiety and thereby reduces the amount of energy given food that would be consumed [26].…”
Section: Discussionmentioning
confidence: 99%